PENERAPAN ALGORITMA ANT COLONY OPTIMIZATION PADA APLIKASI PENJADWALAN MATA KULIAH (Studi Kasus: Program Studi Informatika Fakultas Ilmu Komputer Universitas Pembangunan Nasional Veteran Jakarta) - Andreas Silalahi, (2020)
Scheduling is made so that activities run in a structured manner. One of the scheduling implementations is in scheduling courses. In some educational institutions such as the Universitas Pembangunan Nasional Veteran Jakarta's Program Studi Informatika, scheduling of courses is still done manually. Lots of data that can affect scheduling such as lecturers, students, the amount of space, and the time available makes the process of making schedules not easy and requires a lot of time. This problem can be helped by using and implementing a good algorithm. In this thesis, the course scheduling application combined with the Ant Colony Optimization algorithm will be tested for the course scheduling. In research conducted by other researchers, it was found that the scheduling of courses using Ant Colony Optimization can run effectively and can help reduce problems during the scheduling process.